Do Financial Incentives Influence GPs' Decisions to Do After-Hours Work? A Discrete Choice Labour Supply Model - Barbara Broadway; Guyonne Kalb; Jinhu Li; Anthony Scott (Institute for the Study of Labor (IZA), 2016)
This paper analyses doctors' supply of after-hours care, and how it is affected by personal and family circumstances as well as the earnings structure. We use detailed survey data from a large sample of Australian General Practitioners to estimate a structural, discrete-choice model of labour supply and after-hours care. This allows us to jointly model how many daytime-weekday hours a doctor works, and his or her probability of providing after-hours care. The underlying utility function varies across individual and family characteristics. We simulate labour supply responses to an increase in doctors' hourly earnings, both in a daytime-weekday setting and for after-hours care. Among doctors overall, men and women increase their daytime-weekday working hours if their hourly earnings in this setting increases, but only to a very small extent. Men's labour supply elasticities do not change if their family circumstances change, but for women the small behavioural response disappears completely if they have preschool-aged children. Doctors are somewhat more likely to provide after-hours care if their hourly earnings in that setting increases, but again the effect is very small and is only evident in some sub-groups. Moreover, higher earnings in weekday-daytime practice reduces the probability of providing after-hours care, particularly for men. Increasing doctors' earnings appears to be at best relatively ineffective in encouraging increased provision of after-hours care, and may even prove harmful if incentives are not well-targeted.
Keywords: I11; J22; J44; J21; 330; labour supply; after-hours care; wage elasticity; health workforce; MABEL